Beyond meritocracy: wealth accumulation in the German upper classes - Waitkus, Nora; Groh-Samberg, Olaf (New directions in elite studies, 2017)
This chapter investigates the wealth accumulation patterns of the German upper-middle and upper classes. It examines the role of wealth in the overall capital portfolios of the German upper classes. The chapter refers to Pierre Bourdieu's concepts of capital and the social space to highlight the peculiar features of wealth and incorporate wealth into a general framework of class inequality based on capital portfolios. It discusses conceptual issues of integrating wealth into the analysis of class. The chapter examines multinomial logit regressions of wealth gains or losses on capital portfolios and occupational class. Technical experts are ranged in-between, but with a specific emphasis on meritocracy or even technocracy. Practical scientific knowledge is in a double opposition both to purely intellectual sophistication, which is considered not to pass scientific standards and not down-to-earth, and the rule of economic success, which is, in fact, unpredictable.